The Cultural Dimension of the Concept of Resilience - Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
The resilience concept can be understood as a new approach to the risk challenges of contemporary society. It is especially marked within the young generation. Having in mind the circumstances provoked by the complex globalisation processes, the concept of resilience considers the culturally and contextually related individual capacities for coping with risks and these intensive changes. The paper examines the nature of the defensive factors, as well as their contextual and cultural sensibility and their possible significance beyond their originating Western societies. Considering all the particularities of many contexts of resilience in various national cultures, presumably Western and beyond, is inherent in the analysis of the resilience concept. These resilience and protection factors should be observed as a part of the whole picture, where the individual, and especially societal factors, are highly encouraged by society.